Anchovy (the Engraulidae family) and All of the Potential Aspect: A literature Review - Samsi, Andi Nur; Akhmad, Nur Amaliah; Marlina, Sitti; Rusmidin, Rusmidin (Universitas Labuhanbatu, 2023)
Anchovies are little pelagic fish that are widely distributed in the ocean. This fish has great potential, therefore it must be nurtured. The classic review is the research approach utilized in the literature review. The Mediterranean Sea, Northwest Africa, Bone Bay, Jepara, Ambon Bay, Morocco's Atlantic Coast, Kayeli Bay, Sri Lanka, India, Malaysia, the Red Sea of Eritrea, and Argentina are inhabited to 172 species of anchovy. The catch size, length, and weight of the fish also vary considerably. Seasonal and environmental variables play a significant effect. In certain areas, the potentialsÂ for collecting anchovies can still be expanded while maintaining sustainability. This fish is consumed by the general populace. Comprehensive nutrient profile so that it may be turned into food products (food diversification). Moreover, anchovies include vitamins A, B12, D, and E. Dried anchovies, pepes, tinned anchovies, peanut brittle, fried flour anchovies, cassava/kaoami, biscuits, snacks, chili sauce, infant food additions, and anchovies crispy-sweet are among the several forms of anchovies. By empowering the community, anchovy diversification is accomplished very successfully since it may boost their economic. Anchovy waste may also be converted into fish meal for use as quail feed